Quick response inputs and outcomes in the apparel industry: an example from a South African retailer - White, Gary (School of Economics, 2017)
This paper provides a two-tier framework for empirically analysing Quick Response on a product level. The first part of the framework suggests retail metrics based on the characteristics of Quick Response to allow comparison between supply chains in terms of their adherance ot the strategy. The second section of the framework lays out a methodology for quantifying the benefits of Quick Response by comparing product level performance of Quick Response products to those on traditonal lead times. The suggested methodology is applied to data from a large South African clothing retailer as an example.